Cutaneous Leishmaniasis in Royal Marines from Oruzgan, Afghanistan. Issue 3 (1st September 2012) - Matheson, Andy; Williams, R; Bailey, MS
Abstract : Leishmaniasis is an infectious disease caused by Leishmania protozoa and occurs as a spectrum of clinical syndromes ranging from various forms of cutaneous leishmaniasis (CL) to mucosal leishmaniasis (ML) and visceral leishmaniasis (VL). CL in Afghanistan is either zoonotic (ZCL) due to L. major or anthroponotic (ACL) due to L. tropica and there has been a prolonged epidemic of ACL in eastern Afghanistan since 1987. However, there have been remarkably few reports of CL due to L. tropica amongst foreign troops serving in Afghanistan since 2001. We describe two such cases in Royal Marines deployed to Oruzgan Province in Afghanistan from 2008-9. These patients illustrate important issues regarding the clinical features, referral, diagnosis, treatment and epidemiology of CL amongst foreign troops in Afghanistan. This disease has the potential to cause significant disruption to military personnel and units and so requires efficient management in order to maintain operational effectiveness.